Investigating the Effect of Structure to Structure Separation Distance on Firebrand Accumulation - Suzuki, Sayaka; Manzello, Samuel L. (Frontiers in Mechanical Engineering, 2021)
Wind plays an important role in the built environment. Large outdoor fires in the built environment are no exception. Under strong wind, firebrands fly far, which leads to quick fire spread. In this study, the effect of structure to structure separation distance on firebrand accumulation was investigated by using a custom designed firebrand generator installed in a real scale wind tunnel. Firebrands accumulated at 4 m/s and 6 m/s, but no firebrand accumulation zone was observed at 8 m/s and 10 m/s, regardless of separation distance (SD). Experimental results were compared with a simple CFD flow simulation (no firebrands included). The size of firebrand accumulation zone as well as distance from the structure front was compared with SD in the cases of 4 m/s and 6 m/s wind speeds. It was found that firebrands behave differently from SD = 1 m to 2 m, to that of SD = 2 m to 3 m. The results of this study are the first to explore these important interactions between firebrands and structure separation distances. The results of this work will help develop and design sustainable communities that may better resist the destruction of increasing large outdoor fire outbreaks worldwide.